Glyco-decorated tobacco mosaic virus as a vector for cisplatin delivery. Issue 11 (3rd March 2017) - Liu, Xiangxiang; Liu, Bowei; Gao, Sijia; Wang, Zhaocheng; Tian, Ye; Wu, Man; Jiang, Shidong; Niu, Zhongwei
Abstract : Through the specific recognition of glycoproteins in cell membranes, the glyco-decorated TMV carriers with CDDP show specifically enhanced anti-cancer efficiency. Abstract : Plant viruses have been applied broadly in nanomedical applications profiting from their monodisperse structure, biocompatibility, easy modification, and non-pathogenicity in animals. Here we report a tobacco mosaic virus (TMV) based drug delivery system bearing carbohydrates as targeting ligands. Mannose (Man) and lactose (Lac) moieties were separately conjugated to the exterior surface of TMV (TMV-Man and TMV-Lac) through an efficient copper(i )-catalyzed azide–alkyne cycloaddition. Cisplatin (CDDP), an anticancer drug, was directly loaded into the TMV cavity (CDDP@TMV, CDDP@TMV-Man and CDDP@TMV-Lac) via a metal coordination bond. Through the specific recognition between carbohydrates and glycoproteins in cell membranes, these TMV based vectors show specificity in different cell lines: in the galectin-rich MCF-7 cell line, CDDP@TMV-Man shows enhanced endocytosis and apoptosis efficiency; in the asialoglycoprotein receptor (ASGPR)-overexpressing HepG2 cell line, CDDP@TMV-Lac shows superiority in endocytosis and apoptosis. This research provides a new strategy for tumor-targeted cisplatin delivery.